Cancer-associated fibroblasts in cholangiocarcinoma. Issue 2 (March 2020) - Vaquero, Javier; Aoudjehane, Lynda; Fouassier, Laura
Abstract : Purpose of review: To give a state-of-art knowledge regarding cancer-associated fibroblasts (CAF) in cholangiocarcinoma (CCA) based both on direct evidence and studies on other desmoplastic cancers. High contingency of CAF characterizes CCA, a tumor with a biliary epithelial phenotype that can emerge anywhere in the biliary tree. Current treatments are very limited, the surgical resection being the only effective treatment but restricted to a minority of patients, whereas the remaining patients undergo palliative chemotherapy regimens. In cancer, CAF shape the tumor microenvironment, drive cancer growth and progression, and contribute to drug resistance. All these functions are accomplished through an interplay network between CAF and surrounding cells including tumor and other stromal cells, i.e. immune and endothelial cells. Recent findings: Several studies have pointed out the existence of CAF sub-populations carrying out several and opposite functions, cancer-promoting or cancer-restraining as shown in pancreatic cancer, another prototypic desmoplastic tumor in which heterogeneity of CAF is well demonstrated. Summary: New CAF functions are now emerging in pancreatic and breast cancers like the modulation of immune responses or tumor metabolism, opening new area for treatments.